Distribution and behavior of zinc in estuarine environments: an overview on Bahía Blanca estuary (Argentina) - Marcovecchio, Jorge Eduardo (2016)
Zinc concentrations and distribution have been fully studied within Bahía Blanca estuary, an area which is strongly influenced by urban and industrial stress. Not only metal dissolved in estuarine water were measured but also measured were sediments and suspended particulate matter (SPM), as well as associated with estuarine organisms. In all cases, internationally standardized protocols were applied to metal measurements, including analytical quality check test through analysis of certified reference materials. Total metal contents from surface sediments and SPM were compared with those from a historical database of the area, as well as with values representing the natural geochemical baseline within the system. Results showed that heavy metal pollution is mainly localized in the areas close to both industrial effluents discharge system and urban sewage outfall discharge. Data from sequential extractions indicate that metals from anthropogenic sources are potentially more mobile than those inherited from geological parent material. The influences of other potential sources of metals (i.e., streams, runoff) were also considered. SPM was clearly identified as the main carrier of the studied heavy metals within the system, and its significance to metals input into sediments and/or biota was verified. Zinc has been accumulated within the different biological species from Bahía Blanca estuary, and their kinetics of accumulation have also been considered. Finally, the combination of the obtained results allowed suggesting the maintenance of a surveillance program to assess the environmental quality of this environment.